Digital-Halal Economy in Marketing Finance as The Embodiment of Spiritual Responsibility Strategic Behavioral Accounting - Whedy Prasetyo; Agung Budi Sulistiyo (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose:  This study aims to examine the role of the artificial intelligence-based application digital-halal as a catalyst in financial management. The application represents a form of spiritual corporate responsibility, emphasizing the delivery of added value to consumers. This consumer value reflects the implementation of strategic behavioral accounting principles rooted in digital-halal practices, particularly within the marketing finance context of food and beverage products in Indonesia. Methodology/approach:  A quantitative causality design was employed to analyze the relationship between digital-halal marketing finance practices and spiritual responsibility. The study operationalized specific criteria for the utilization of the digital-halal economy as a measurable construct in corporate financial strategies. Data were collected from 25 food and beverage companies listed on the Indonesian Stock Exchange. Findings: The study reveals a two-way causal relationship between the digital-halal economy and spiritual responsibility among food and beverage companies listed on the Indonesia Stock Exchange. This reflects the application of strategic behavioral accounting in marketing finance, where digital-halal practices embody consumer-driven values and reinforce spiritual responsibility as a foundation for core advantage. Practical implications: Integrating digital-halal aspects into product marketing reflects strategic behavioral accounting that enhances consumer value. These aspects highlight the benefits of food and beverage products while reinforcing spiritual responsibility as a basis for achieving core advantage. Originality/value: This study offers originality by framing product marketing as a core value within strategic behavioral accounting, guided by digital-halal principles as a form of spiritual responsibility. This connection enhances consumer value and strengthens the link between accounting and marketing in achieving core advantage.